Penerapan Pendekatan Matematika Realistik Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Sarbiyono, Sarbiyono (UIN Sunan Ampel Surabaya, 2016)
This paper discusses of difference to increasing ability of mathematical problem solving of students who obtain realistic mathematics approach and students who received conventional methods. Subject of this research are X.I as experimental class and X.G as controls class, in which every class consist of 40 students. The instrument used to measure the ability of a test of problem solving is a five essay test. While the analysis used in the study were different test average. The conclusion of this study are: mathematical problem solving ability of students who obtain realistic mathematics learning is higher than the mathematical problem solving ability of students who acquire learning by conventional methods.